Implementasi Usaha Kesehatan Sekolah (UKS) dalam Pengendalian Demam Berdarah di Kecamatan Pangandaran - Joni Hendri (Inovasi, 2020)
School-age children are part of the social elements that have a great opportunity as one of the agents of change. Besides, school-age children have a risk of dengue transmission. Seeing this opportunity, in 2014 the Ministry of Health made technical guidelines for the implementation of “Jumantik-PSN” for school children. This is based on the issuance of the Joint Decree (SKB) of four ministers in the same year. The implementation of the program is closely related to the ability of local governments to maximize resources and available facilities and infrastructure. The aim of this study was to evaluate School Health Program activities in implementing the dengue vector control program in accordance with “Jumantik-PSN” Technical Guidelines for school children. A mixed-method design was used by combining quantitative with qualitative methods. The study was carried out in 44 schools. The results showed that there was a risk of dengue transmission in schools with the number of larva free was 75%. Health School Programs activities do not yet support in dengue vector control program. The obstacles of implementation of this program include knowledge, Budget, Facilities and across sectors cooperation. Supporting factor includes a positive attitude of program implementers and technical means of implementation available. The study concluded that the “Jumantik-PSN” Program for school children has not been implemented properly. Keywords: Jumantik, vector control, Health School Programs, Implementation